(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
English occupies an important place in the world today. It seems obvious that it is impossible to teach all the knowledge, skills, methods, techniques, which are of potential use to teachers. The main aim of the article is to study the problem of developing listening comprehension skills for B2 level learners. It seems advisable to teach the teachers and caregivers in such a way as to strengthen their dispositions go on learning, to be resourceful and to be inventive.